Pengawasan Pada Wilayah Perbatasan Negara Menurut Hukum Internasional - Suitela, Autin Christani; Tahamata, Lucia Charlota Octovina; Leatemia, Wilshen (TATOHI: Jurnal Ilmu Hukum, 2024)
Introduction: The border problem has complex dimensions. There are a number of crucial factors involved in it such as jurisdiction and state sovereignty, politics, socio-economics, and defense and security but there are still many violations in the border area.Purposes of the Research:  Analyzing and knowing Regulations Concerning Surveillance in Border Areas According to International Law and the government's function of surveillance in border areasMethods of the Research: This research uses a normative juridical method with the legal materials used in the research are primary, secondary and tertiary with the use of library study techniques in the form of criminal law regulations, scientific works and literature.Results of the Research: The function of the Government in dealing with problems in border areas, the Indonesian government creates institutions that carry out supervisory functions and involve several law enforcement officials in dealing with problems in border areas, namely the Ministry of Maritime Affairs, BAKAMLA, TNI-AL, BNPP, POLRI, POLRI POLOAIR, and the establishment of posts crossing borders, strengthening the TNI in border areas, and building surveillance posts in dealing with problems in border areas which is a form of government in dealing with problems in border areas and is a form of law enforcement carried out by the government.